"Because I saw my mother cooking": the sociocultural process of learning and teaching domestic culinary skills of the Western Brazilian Amazonian women. Issue 4 (2nd October 2022) - da Silva Oliveira, Mayara Sanay; Fernandez Unsain, Ramiro Andres; Morais Sato, Priscila de; Ulian, Mariana Dimitrov; Scagliusi, Fernanda Baeza; Cardoso, Marly Augusto
Abstract: This article describes and discusses the sociocultural process of learning and teaching women's domestic culinary skills. Drawing on descriptive qualitative research, we conducted an in-depth analysis of semi-structured interviews with 16 cisgender women who cooked at home at least once a day and lived in Cruzeiro do Sul, Acre state, Brazilian Western Amazon. Our results suggest that women develop their domestic cooking skills at different moments. In childhood, the women interviewed were taught by their maternal figures and learned the required culinary skills to prepare "Rainforest Foods, " traditional foods in their original places. In adulthood, female employers taught them the culinary skills needed to prepare "City food, " meals made with ingredients, tools, and cooking methods available in the urban area. Notably, the women interviewed also reported being taught by their husbands to cook foods that met their tastes and eating patterns. In contrast, women teach their sons and daughters culinary skills to develop their food autonomy and promote the egalitarian division of domestic culinary work. These findings are essential to understand the sociocultural process of learning and teaching domestic culinary skills among communities or membership groups who lived in forest or rural areas and migrated to urban centers.